Pengaruh Profitabilitas, Leverage, dan Tax Avoidance terhadap Nilai Perusahaan pada Perusahaan Perkebunan Kelapa Sawit di BEI (2020–2024) - Shaprilia Paramitha Sirait; Timbul Hamonangan Simanjuntak; Rutman Lumbantoruan (Journal of Economic and Business Advancement, 2026)
This study aims to examine the causal relationship between profitability, leverage, and tax avoidance on firm value in the palm oil plantation subsector listed on the Indonesia Stock Exchange during the 2020–2024 period. The research employs a quantitative empirical approach using panel data regression to capture both cross-sectional and time-series dynamics. The results indicate that profitability does not have a significant effect on firm value, suggesting that increased earnings are not necessarily perceived positively by the market without operational efficiency and earnings quality. In contrast, leverage shows a significant positive effect, implying that optimal debt utilization serves as a positive signal for investors regarding firm growth and expansion potential. Tax avoidance is found to have no significant impact on firm value, indicating that tax strategies are not a primary consideration for market valuation in this context. These findings highlight the importance of integrated financial decision-making in enhancing firm value.